Antimicrobial resistance trends of Escherichia coli and Staphylococcus aureus isolated from clinical blood cultures in Namibia: a nine-year (2011-2019) retrospective study - Haindongo, Erastus Hanganeni H.; Hakanen, Antti J.; Vainio, Olli; Vuopio, Jaana; Hedimbi, Marius (BioMed Central, 2026)
Background:
Due to inadequate data on the antimicrobial resistance situation among the two predominant bacteremia-causing pathogens, the objective was to analyze the nine-year antimicrobial resistance trends of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) from blood cultures.
Methods:
A nine-year countrywide register data (2011–2019) covering all microbiological specimen tests performed at the Namibia Institute of Pathology (NIP) were analyzed. Antimicrobial susceptibility testing (AST) was performed by disk diffusion and VITEK-2, along with Quality Control parallels to validate AST results. This was interpreted in accordance with the prevailing CLSI breakpoints. Data analysis included descriptive statistics and chi-square, Multiple Antibiotic Resistance (MAR) Index and Mann-Kendall trend tests (α = 0.05).
Results:
The original findings comprised 30,266 bacterial organisms isolated from 37,765 blood cultures. After adjusting for putative contaminants, the Gram-negative bacterial species (GNB) group comprised most of the major findings, including E. coli (15.2%), K. pneumoniae (13.2%), S. enterica (3.2%), and P. aeruginosa (2.8%). S. aureus (15.3%) and E. faecalis (6.5%) comprised the majority of gram-positive bacterial (GPB) organisms. E. coli and S. aureus were commonly isolated from the 15–59 and 0–4 age groups, respectively. Significant upward trends (for amoxicillin-clavulanate and 3rd generation cephalosporins) and downward trends (oxacillin and gentamicin) were found. In 2019, the following resistance to E. coli were observed: ceftriaxone (37%), ciprofloxacin (29.4%), gentamicin (18.8%), and meropenem (0.9%). In 2019, S. aureus resistance to oxacillin was 18.8%. The proportions of ESBLs increased from 22.1% (n = 79) to 42% (n = 116) (ss:1.75, p = 0.03). Whilst methicillin-resistant S. aureus (MRSA) reduced from 47.2% to 18.8% in 2019 (ss: −2.05, p = 0.03). The proportion of multi-drug resistant E. coli increased to 47.8% (p < 0.01), whilst extensive-drug resistant E. coli decreased to 3% (p = 0.04) and no potential pan-drug resistant organisms were found.
Conclusions:
To our knowledge, this is the first study to provide a 9-year insight into the trends of antimicrobial resistance in clinical blood culture isolates in Namibia. ESBLs showed an increasing trend, whilst MRSAs declined due to potential improvements in infection prevention & control (IPC) and antimicrobial stewardship. Resistance levels of above 20% to critical antimicrobials (i.e. amoxicillin-clavulanate, ceftriaxone, ciprofloxacin, and erythromycin) is worrying for the management of bloodstream infections caused by ESBLs or MRSAs. Overall, this study serves as a baseline for future surveillance work and highlights the continuous need for AST-guided therapy.